Peningkatan prestasi belajar seni budaya melalui penerapan model pembelajaran problem based learning - Made Ciriani (Indonesian Journal of Educational Development, 2021)
The study was conducted in SMK Negeri 2 Singaraja in10 grade students of Hotel Accommodation that students' ability to cultural art material are fairly low. The purpose of the study for this class is to know what the Problem Based Learning, is able to increase achievement students' learning.  The data collected method is from achievement students' test. The analysis data method is descriptive both of qualitative and quantitative data. The result of the study is there has been changed of achievement for 10 grade students of Hotel Accommodation after the implementation of Problem Based Learning method.  It is evident from the result that achieve at first students' average is 68.07, next up in first Cycle increased to 75,26. From the first cycle of the second cycle average goes up to 84,32. The conclusions drawn from the study are the Problem Based Learning model able to increase student achievement in culture, art material in 10 grades of Accommodation Hotel in SMK Negeri 2 Singaraja in the second semester in year of lesson 2018/2019. Penelitian ini dilaksanakan di SMK Negeri 2 Singaraja dengan subjek peneliaian adalah siswa Kelas X Akomodasi Perhotelan-1 yang kemampuan siswanya untuk mata pelajaran seni budaya cukup rendah. Objek penelitian adalah prestasi belajar seni budaya. Tujuan penelitian tindakan kelas ini adalah untuk mengetahui apakah model pembelajaran Problem Based Learning dapat meningkatkan prestasi belajar seni budaya. Instrumen pengumpulan datanya adalah tes prestasi belajar. Metode analisis datanya adalah deskriptif baik untuk data kualitatif maupun untuk data kuantitatif. Hasil yang diperoleh dari penelitian ini adalah terjadi perubahan prestasi belajar siswa kelas X Akomodasi Perhotelan-1 setelah penerapan model pembelajaran Problem Based Learning. Ini terbukti dari hasil yang diperoleh pada awalnya prestasi belajar siswa rata-rata 68,07 selanjutnya pada siklus I meningkat menjadi 75,26. Dari Siklus I ke Siklus II rata-rata naik menjadi 84,32. Kesimpulan yang diperoleh dari penelitian ini adalah model pembelajaran Problem Based Learning dapat meningkatkan prestasi belajar seni budaya siswa Kelas X Akomodasi Perhotealan-1 SMK Negeri 2 Singaraja Semester Genap Tahun Pelajaran 2018/2019.